Readiness of Students to Work on Tasks During the Covid-19 Pandemic - Reski, Dinda Jengtika; Ilyas, Asmidir (Current Issues in Counseling, 2021)
Readiness to learn is the overall condition of a person who makes him ready to give a response or answer in the learning process. The learning process will run well if it is supported by several things, including: readiness to learn, do assignments, read, and so on. This study aims to: (1) describe the level of readiness of students to do assignments, (2) describe the forms of students' difficulties in doing assignments, and (3) the role of BK teachers to overcome students' difficulties in doing assignments at SMA N 11 Padang. This study uses a quantitative approach with descriptive research methods. The research subjects were students of SMA N 11 Padang at the level of class X, and XI totaling 224 people. Collecting data using a Likert scale model questionnaire, the data were analyzed using percentage analysis techniques. The results of the study revealed that: (1) the readiness of students to do assignments in the aspect of understanding the task was in the quite ready category with an achievement score of 60.7%, (2) the readiness of students to do assignments in the aspect of providing resources was in the quite ready category with an achievement score of 62, 5%, (3) the readiness of students to do assignments in the aspect of task completion is in the quite ready category with an achievement score of 57.6%, (4) the readiness of students to work on assignments in the aspect of assignment submission is in the category of quite ready with an achievement score of 70%.